2017
DOI: 10.1002/ange.201612471
|View full text |Cite
|
Sign up to set email alerts
|

Brønsted Acid Catalyzed Oxygenative Bimolecular Friedel–Crafts‐type Coupling of Ynamides

Abstract: Scheme 1. Brønsted acid-catalyzed a-oxo carbene equivalent.Supportinginformation and the ORCID identification number(s) for the author(s) of this article can be found under: http://dx.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 89 publications
(17 reference statements)
1
7
0
Order By: Relevance
“…in 1,2‐dichloroethane produced the α‐chloroenamide 14 (Scheme B), and concluded that the formation of the adduct 16 from V is reversible above 80 °C. As was next found in the case of stronger acid catalysts (HNTf 2 ), the keteniminium ion V forms the adduct VI with N‐ oxide adduct at room temperature, presumably in a reversible manner. Interestingly, over‐oxidation to 17 by the second attack of N‐ oxides did not interfere.…”
Section: Intermolecular Addition Of Nucleophilessupporting
confidence: 60%
See 1 more Smart Citation
“…in 1,2‐dichloroethane produced the α‐chloroenamide 14 (Scheme B), and concluded that the formation of the adduct 16 from V is reversible above 80 °C. As was next found in the case of stronger acid catalysts (HNTf 2 ), the keteniminium ion V forms the adduct VI with N‐ oxide adduct at room temperature, presumably in a reversible manner. Interestingly, over‐oxidation to 17 by the second attack of N‐ oxides did not interfere.…”
Section: Intermolecular Addition Of Nucleophilessupporting
confidence: 60%
“…Brønsted acid‐catalyzed oxidative coupling enabled incorporation of a diverse range of nucleophiles in this Friedel‐Crafts alkylation. Not only indoles, pyrroles, and anilines, but also phenols as well as silyl enol ethers were found to be excellent nucleophilic partners . In terms of regioselectivity, alkylation occurred exclusively at the para‐ position of the phenolic OH.…”
Section: Intermolecular Addition Of Nucleophilesmentioning
confidence: 99%
“…We then investigated other non-noble metals (Table 1 , entries 2−6), and were pleased to find that Cu(CH 3 CN) 4 PF 6 catalyzed the oxidative cyclization to produce the desired 2a in 41% yield (Table 1 , entry 6). Of note, rhodium (Table 1 , entry 7) 35 and Brønsted acids 56 59 such as TsOH and TfOH were not effective in promoting this reaction (for more details see Supplementary Table 1 ). Interestingly, pyrrolo[2,3- b ]indole 3a was obtained as the main product in the presence of typical gold catalysts such as Ph 3 PAuNTf 2 and IPrAuNTf 2 (Table 1 , entries 8 and 9).…”
Section: Resultsmentioning
confidence: 99%
“…Pleasingly, after brief examination of the reaction conditions, we found that the reaction of 1 a and 2 a catalyzed by a cationic gold catalyst IPrAuNTf 2 (IPr=1,3‐bis(diisopropylphe nyl)imidazol‐2‐ylidene) in 1,4‐dioxane could proceed smoothly at 80 °C, and the target tetracyclic spiroindoline 3 a was isolated in nearly quantitative yield. Control experiments further highlight the critical role of the cationic nature for the gold catalyst, and Brønsted acid HNTf 2 was not efficient as well (Scheme ).…”
Section: Figurementioning
confidence: 99%